2017
DOI: 10.3346/jkms.2017.32.8.1263
|View full text |Cite
|
Sign up to set email alerts
|

Recovery Rates of Non-Tuberculous Mycobacteria from Clinical Specimens Are Increasing in Korean Tertiary-Care Hospitals

Abstract: Non-tuberculous mycobacteria (NTM) are being recognized increasingly as the causative agents of opportunistic infections in humans. This study investigated the epidemiologic trends of NTM recovery from various clinical specimens in 2 Korean tertiary-care hospitals. We reviewed the laboratory records of patient samples cultured for mycobacteria between 2009 and 2015 at 2 tertiary-care hospitals in Korea. The medical records for patients with positive NTM samples were also reviewed. During the study period, 144,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 19 publications
2
22
0
Order By: Relevance
“…The epidemiology of NTM pulmonary disease or infections has remained largely unclear in Korea. However, recent NTM epidemiology studies have shown that NTM pulmonary disease or infections are increasing steadily [17, 21, 22]. One study conducted in two Korean tertiary-care hospitals reported that the incidence of NTM pulmonary disease increased from 6.8 per 100,000 patients in 2009 to 12.9 per 100,000 patients in 2015 [21].…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiology of NTM pulmonary disease or infections has remained largely unclear in Korea. However, recent NTM epidemiology studies have shown that NTM pulmonary disease or infections are increasing steadily [17, 21, 22]. One study conducted in two Korean tertiary-care hospitals reported that the incidence of NTM pulmonary disease increased from 6.8 per 100,000 patients in 2009 to 12.9 per 100,000 patients in 2015 [21].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the increasing number of annual NTM isolates and the significant clinical relevance [2022]. In Korea, the incidence of pulmonary NTM disease has doubled in 2015 compared to the number in 2009 [23, 24]. Japan revealed that NTM disease has reached 14.7 cases per 100, 000 people-years [25] .…”
Section: Introductionmentioning
confidence: 99%
“… 6 In Korea, previous studies showed that the NTM isolation rate and the number of patients with NTM-LD have increased steadily. 7 8 9 10 11 12 However, the long-term trend of the changes of causative organisms of NTM-LD was not available in Korea.…”
mentioning
confidence: 99%